Co-occurrence of Tubular Apocrine Adenoma and Syringocystadenoma Papilliferum over the Hypogastrium: A Rare Case Report - R Raghunatha Reddy; Mukunda Ranga Swaroop; Yogesh Devaraj; Greeshma Jagadish; Namratha Govindaraju (Clinical Dermatology Review)
Tubular apocrine adenoma (TAA) and syringocystadenoma papilliferum (SCAP) are rare benign sweat gland tumors. To date, only 17 cases of their coexistence have been reported worldwide. A 16-year-old female patient presented with multiple linearly arranged pink pedunculated grouped papules and plaques with irregular and lobulated surfaces present over the hypogastrium region for 6 years. There was no evidence of nevus sebaceous. A complete excision of the tumor was performed. On histopathology upper dermis showed cystic invagination lined by outer columnar and innercuboidal epithelium extending downward from the epidermis with papillary projections suggestive of SCAP, and the lower dermis revealed apocrine glands lined by double-layered epithelium with luminal decapitating secretions suggestive of TAA, thereby confirming the coexistence.